Racial Residential Segregation in the United States - Logan, Trevon D.; Parman, John M. (Journal of Economic Literature, 2025)
Residential segregation is a central factor in explaining socioeconomic gaps across race and ethnicity in the United States. Place of residence directly impacts access to schools, jobs, and health care. There is an ever-evolving literature across the social sciences disciplines documenting the general patterns in residential segregation as well as the causes and consequences of those patterns. This article reviews key parts of that literature. We provide an overview of the measurement of segregation and the general evolution of segregation patterns over time and at different scales. We then review the literatures on both segregation’s determinants and its impact on a range of socioeconomic outcomes. We highlight the potential for new insights to be gained from new approaches to quantifying segregation and new frameworks such as stratification for understanding its complex roots. (JEL D72, I24, I32, J15, R23, R28)